2006
DOI: 10.5194/acp-6-883-2006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling molecular iodine emissions in a coastal marine environment: the link to new particle formation

Abstract: Abstract.A model of iodine chemistry in the marine boundary layer (MBL) has been used to investigate the impact of daytime coastal emissions of molecular iodine (I 2 ). The model contains a full treatment of gas-phase iodine chemistry, combined with a description of the nucleation and growth, by condensation and coagulation, of iodine oxide nano-particles. In-situ measurements of coastal emissions of I 2 made by the broadband cavity ring-down spectroscopy (BBCRDS) and inductively coupled plasmamass spectrometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
173
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 53 publications
11
173
2
Order By: Relevance
“…The source is most probably exposure of macroalgae, which induces emission of I 2 , ultimately leading to formation of iodine oxide particles as has been reported in the past (O'Dowd et al, 2002;Saiz-Lopez et al, 2006;McFiggans et al, 2010). As mentioned above, a macroalgal belt, 30-50 m wide, was observed within the intertidal zone adjacent to the measurement site along the coast.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The source is most probably exposure of macroalgae, which induces emission of I 2 , ultimately leading to formation of iodine oxide particles as has been reported in the past (O'Dowd et al, 2002;Saiz-Lopez et al, 2006;McFiggans et al, 2010). As mentioned above, a macroalgal belt, 30-50 m wide, was observed within the intertidal zone adjacent to the measurement site along the coast.…”
Section: Discussionmentioning
confidence: 73%
“…In the past, studies at other coastal locations have reported a daytime maximum of 25-29 pptv through integrated long-path differential optical absorption spectroscopy (LP-DOAS) measurements at Mace Head (Saiz-Lopez and Huang et al, 2010), 115 pptv using in situ measurements at Mace Head (Saiz-Lopez et al, 2006), 87 pptv at Mweenish Bay-I and 302 pptv Mweenish Bay-II, both close to Mace Head using in situ techniques (Huang et al, 2010), 32 pptv (integrated) and 50 pptv (in situ) at Roscoff (Mahajan et al, 2009;McFiggans et al, 2010), and 3 pptv (in situ) at Scripps Pier, La Jolla, California (Finley and Saltzman, 2008). The peak I atom mixing ratio of 10 ± 5 pptv is lower than a maximum of 22 pptv reported by Bale et al (2008) at Mace Head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine radicals can also self-react to form iodine oxides such as I 2 O 4 and other larger iodine oxide clusters (McFiggans et al, 2004;Saiz-Lopez et al, 2006). If iodine levels are sufficiently high, the formation of iodine oxides leads to rapid particle nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Since molecular iodine and iodocarbons are photochemically unstable (lifetimes between about some tens of seconds for I 2 and a few days for CH 3 I), they are photolysed under UV-visible light to form I· atoms, which are then instantly oxidized by ozone to form the iodine monoxide radical IO (g) (Hoffmann et al, 2001;Saiz-Lopez et al, 2006). Further oxidation reactions of IO in the gas phase then can form low-volatility iodine oxides (I x O y ) which may nucleate under certain conditions and form new particles.…”
mentioning
confidence: 99%